Peningkatan Kompetensi Pegawai Dalam Menyusun Dan Melaksanakan Standar Operasional Prosedur Melalui Tahapan Nadime - Mardiningsih, Heni (Balai Diklat Keagamaan Surabaya, 2020)
The purpose of this study was to determine the stages of Need Assessment, Development, Implementation, Monitoring and Evaluation to improve employee competence in compiling and implementing SOP at MTsN 3 Ponorogo. The method used in this research is descriptive qualitative. Based on the phenomena described in natural words based on interview, observation and documentation techniques. The results of the research analysis state that there is a gradual increase in employee competence in compiling and implementing SOPs significantly, through the initial stages of understanding the concept of SOP preparation and development based on the Ministry of Religion's technical guidelines number 168 of 2010, increasing the ability to identify SOP needs, establishing an SOP development team to obtain input from information from users of madrasah services as well as refining SOPs, implementing SOPs in daily tasks at madrasahs and conducting monitoring and evaluation in monitoring SOP implementation.